MARINE ALGAE COLLECTED DURING THE MARINE BIODIVERSITY MINI EXPEDITION 2012 TO SEMBILAN GROUP OF ISLANDS, PERAK WITH ONE NEW RECORD, Parvocaulis parvulus (Solms-Laubach) S. Berger et al. FOR MALAYSIA - Yeong, Hui-Yin; Draisma, Stefano G. A.; Phang, Siew-Moi (Malaysian Journal of Science, 2012)
In May 11 -15, 2012, the Institute of Ocean and Earth Sciences, University of Malaya organized a marine expedition to the Sembilan Group of Islands, Perak (Malaysia). The objective of the expedition was to document the marine biodiversity in the waters around the islands and the coastal zone as well as documenting physical parameters. Marine algae were among the targeted groups of taxa. A total of 51 algal specimens were collected. All specimens are deposited as herbarium in the University of Malaya Seaweed and Seagrass Herbarium. The algae comprised one family, one genus and three putative species of Cyanophyta; five families, six genera and 13 putative species of Chlorophyta; seven families, ten genera and 13 putative species of Rhodophyta and one family, one genus and one putative species of Phaeophyceae. Of these, the chlorophyte Parvocaulis parvulus (Solms-Laubach) S. Berger et al. is a new record for Malaysia. In 2008, Phang et al. reported that a total of seven families and nine putative species of marine algae were collected during the Scientific Expeditions to the Seas of Malaysia (SESMA) I and II from the Sembilan Group of Islands (Pulau Lalang and Pulau Rumbia) Perak. Of these, an addition of six families and 11 putative species were collected during this present survey. ABSTRAK Pada Mei 11-15, 2012, Institut Sains Samudera Dan Bumi, Universiti Malaya telah mengelolakan satu ekspedisi marin ke Kepulauan Sembilan, Perak, Malaysia. Objektif expedisi ini adalah untuk mendokumentasikan biodiversiti marin serta parameter fikizal di kawasan perairan persekitaran dan juga di zon persisiran pantai kepulauan ini. Alga marin merupakan salah satu kumpulan taksa sasaran tinjauan ini. Sejumlah 51 spesimen alga telah dikutipkan. Semua specimen ini telah disimpankan sebagai herbarium di dalam Herbarium Rumpair dan Rumput Laut Universiti Malaya. Alga tersebut merangkumi satu famili, satu genus dan tiga spesies putatif Cyanophyta; lima famili, enam genera dan 13 spesies putatif putative Chlorophyta; tujuh famili, sepuluh genera dan 13 spesies putatif Rhodophyta dan satu famili, satu genus dan satu spesies putatif Phaeophyceae. Di antara ini, chlorophyte Parvocaulis parvulus (SolmsLaubach) S. Berger et al. merupakan rekod baru bagi Malaysia. Pada tahun 2008, Phang et al. melaporkan bahawa sejumlah tujuh famili dan sembilan spesies putatif alga marin telah dikutipkan dari Kepulauan Sembilan (Pulau Lalang and Pulau Rumbia), Perak dalam Ekspedisi Saintifik ke Lautan Malaysia (SESMA) I dan II. Berbanding dengan ini, sebanyak enam famili dan 11 spesies putatif tambahan telah dikutipkan dalam ekspedisi tinjauan baru ini. (Keywords: marine algae, checklist list, Sembilan Group of Islands)